Enhancing Teacher Professionalism through Organizational Citizenship Behavior (OCB): The Role of Principal Leadership in Junior High School - Sarjito; Ngurah Ayu Nyoman; Muhammad Prayito (IQRO: Journal of Islamic Education, 2024)
This study aims to analyze the role of school principals in developing Organizational Citizenship Behavior (OCB) to enhance teacher professionalism at SMP Negeri 3 Batang. A qualitative phenomenological approach was employed. Data were collected through in-depth interviews, observations, and documentation, and analyzed using triangulation techniques. The findings reveal three key aspects of the principal’s role: (1) planning, by integrating OCB values into school programs; (2) implementation, through teachers’ voluntary practices such as assisting colleagues, supporting school activities, and engaging beyond formal duties; and (3) monitoring, carried out via academic supervision, evaluations, and recognition of proactive teachers. The study concludes that the application of OCB significantly strengthens teacher professionalism in pedagogical, social, and professional dimensions. These findings underscore the significance of school leadership as a crucial strategy for enhancing educational quality.